The Effects of Experience and Task – Specific Knowledge on Auditors’ Performance in Assessing A Fraud Case - Rio Tirta; Mahfud Sholihin (Jurnal Akuntansi dan Auditing Indonesia, 2004)
The objective of this study is to investigate the relationships of auditors’ experience, knowledge, and performance. Specifically, it examined whether the task-specific knowledge variable could affect the relationship between the auditor’s experience and performance in assessing a fraud. The study hypothesized that task-specific knowledge will improve auditors’ performance in a fraud risk task. Additionally, it hypothesized that the combination of experience and fraud training would improve auditors’ performance in assessing the task. Using a sample of 64 auditors and 42 students, as expected, the study provided support for the hypotheses.Key words: Auditors’ experience; task-specific knowledge; auditors’ performance; fraud.